An Appraisal of Indoor Thermal Comfort in a Naturally Ventilated Modified Old Mosque in Banda Aceh, Indonesia - Rini Try Novita; Laina Hilma Sari; Ardian Ariatsyah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
A traditional mosque is a form of conformity between the design and the climate. The warm humid climate in Indonesia characterizes the environment, which is quite challenging to work with. The traditional mosque, with the uniqueness of the roof design, allows the application of a natural ventilation system that can work effectively in circulating air to reduce the effect of heat in the room. However, the application of the design has rarely been found in modern mosques due to the widespread use of the dome. This study appraised Tgk Dianjong Mosque, one of the old mosques in Banda Aceh, Indonesia. The old mosque was modified by replacing the roof material and ventilation. This study aims to appraise the indoor thermal comfort of the mosque considering the application of natural ventilation. The method used in this research is descriptive quantitative, with research data collected through physical measurements, i.e., air temperature, relative humidity, and air velocity. The collected data were analyzed using the CET (Corrected Effective Temperature) index and assessed based on SNI 03-6572-2001. Multiple linear regression analysis was conducted to determine how much wind speed influences the thermal condition of the mosque. The study was conducted for two days, with the selected time being in the morning, afternoon, and evening to obtain more varied data. This study performs that the renovation of replacing the roof ventilation with fixed glass would contribute to the lack of airspeed throughout the mosque. The old material of the roof, i.e., leaf grass, was displaced with a metal roof, creating a highly effective temperature and hence indicated as uncomfortable.